The Mexican Scale of Languages: stakeholders’ voices of its socio-political impact - González, Elsa Fernanda; Zheng, Ying; De la Garza-Cano, Ricardo; Morales-Berlanga, Lizbeth (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
The National Certificate of Language Proficiency (CENNI) is a Mexican language scale developed by the Ministry of Education to validate citizens’ language skills. This study aimed to analyze the socio-political impact of the CENNI in Mexico in regards to its uses, its impact on professional development, political decisions and language development in the country. Five CENNI stakeholders took part in the study, including language teachers and one national decision-maker from the federal administration of the CENNI. Semi-structured interviews conducted with participants suggested that stakeholders hold different views on the multiple uses of the CENNI and its nature. While teachers considered it a “test” or a “required process” , the national stakeholder viewed it as a tool that could contribute to a candidate’s language proficiency. The study provides possible implications for CENNI candidates, language assessment policy makers in the country and around the world.